Increase in computed tomography in Australia driven mainly by practice change: A decomposition analysis - Wright, Cameron; Bulsara, M.; Norman, R.; Moorin, R. (Elsevier Ireland Ltd, 2017)
Background: Publicly funded computed tomography (CT) procedure descriptions in Australia often specify the body site, rather than indication for use. This study aimed to evaluate the relative contribution of demographic versus non-demographic factors in driving the increase in CT services in Australia. Methods: A decomposition analysis was conducted to assess the proportion of additional CT attributable to changing population structure, CT use on a per capita basis (CPC, a proxy for change in practice) and/or cost of CT. Aggregated Medicare usage and billing data were obtained for selected years between 1993/4 and 2012/3. Results: The number of billed CT scans rose from 33 per annum per 1000 of population in 1993/94 (total 572,925) to 112 per 1000 by 2012/13 (total 2,540,546). The respective cost to Medicare rose from $145.7 million to $790.7 million. Change in CPC was the most important factor accounting for changes in CT services (88%) and cost (65%) over the study period. Conclusions: While this study cannot conclude if the increase is appropriate, it does represent a shift in how CT is used, relative to when many CT services were listed for public funding. This ‘scope shift’ poses questions as to need for and frequency of retrospective/ongoing review of publicly funded services, as medical advances and other demand- or supply-side factors change the way health services are used.